Combination of 2D and 3D vision systems into robotic cells for improved flexibility and performance - Sansoni, G.; Bellandi, P.; Docchio, F. (2011 4th IEEE International Workshop on Advances in Sensors and Interfaces, 2011)
In this paper we present the research activity carried out in the integration of 2D and 3D vision systems into robot cells, to improve their performance in typical pick and place operations. Two projects have been developed: the former is the combination of a 2D vision system based on two cameras with a two-robot cell. The latter consists of the integration of a laser slit - based optical head in a robot arm, for the 3D recognition of pose and orientation of objects, in view of bin picking applications. Both projects were committed by DENSO EUROPE B. V. with the aim of improving the robots performances in terms of flexibility and robustness of operation.